Development of primary design guidelines for supportive underwear to elevate the bladder neck in women based on finite element analysis of the pelvis. (February 2022) - Tawara, Daisuke; Nishiki, Tomohiro; Ninomiya, Sanae; Okayama, Hisayo; Naito, Kiyoko; Morikawa, Shigehiro
The use of supportive underwear has been applied for preventing stress urinary incontinence (SUI) which is caused by descent of the bladder neck due to weakness in the pelvic floor muscles, because it is known that SUI can be improved by elevating the descended bladder neck. However, appropriate approaches to the underwear design are still being explored. In order to establish an appropriate first-order design strategy for supportive underwear, clarifying the relationship between the pressure from the underwear and the amount of elevation of the bladder neck is necessary. We constructed a finite element model of the pelvis based on magnetic resonance images of a subject in an upright position, experimentally explored Young's modulus of the soft tissue and analyzed the amount of elevation of the bladder neck when changing the combination of applied pressures from the underwear. The position of the bladder neck relatively elevated when the pressure in the region from the abdomen to the pubis decreased and when the pressure in the region from the perineum to the coccyx increased, suggesting an appropriate design for the supportive underwear.